The best of Comedy Central presents [videorecording (DVD)]. - Black, Lewis; Cook, Dane; Dunham, Jeff, 1962-; Hedberg, Mitch, 1968-2005; Mencia, Carlos; Regan, Brian (Paramount Home Entertainment, 2008)
Features some of the hottest comics shown on Comedy Central Presents. Includes performances by Lewis Black, Dane Cook, Jeff Dunham, Jim Gaffigan, Mitch Hedberg, Demetri Martin, Carlos Mencia, Brian Regan, and more.